Clinicopathological Features and Prognostic Factors Affecting Survival Outcomes in Isolated Locoregional Recurrence of Breast Cancer: Single-Institutional Series - Lee, Min-Young; Chang, Won Jin; Kim, Hae Su; Lee, Ji Yun; Lim, Sung Hee; Lee, Jeong Eon; Kim, Seok Won; Nam, Seok Jin; Ahn, Jin Seok; Im, Young-Hyuck; Park, Yeon Hee (PLOS ONE, 2016)
Purpose The purpose of this study was to investigate the clinicopathologic features and prognostic factors affecting outcome in patients with isolated locoregional recurrence of breast cancer (ILRR). Methods We retrospectively analyzed the medical records of 104 patients who were diagnosed with ILRR and underwent curative surgery from January 2000 to December 2010 at Samsung Medical Center. Results Among 104 patients, 43 (41%) underwent total mastectomy and 61 (59%) underwent breast-conserving surgery for primary breast cancer. The median time from initial operation to ILRR was 35.7 months (4.5–132.3 months). After diagnosis of ILRR, 45 (43%) patients were treated with mastectomy, 41 (39%) with excision of recurred lesion, and 18 (17%) with node dissection. During a median follow-up of 8.9 years, the 5-year overall survival was 77% and 5-year distant metastasis-free survival (DMFS) was 54%. On multivariate analysis, younger age (< 35 years), higher stage, early onset of elapse (≤ 24 months), lymph node recurrences, and subtype of triple negative breast cancer (TNBC) were found to be independently associated with DMFS. Patients in the no chemotherapy group showed a longer DMFS after surgery for ILRR than those treated with chemotherapy (median 101.5 vs. 48.0 months, p = 0.072) but without statistical significance. Conclusion Our analysis showed that younger age (< 35 years), higher stage, early onset of relapse (≤ 24 months), lymph node recurrence, and subtype of TNBC are the worst prognostic factors for ILRR.